2023
DOI: 10.3390/ijerph20032486
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Winery Wastewater by Combined Almond Skin Coagulant and Sulfate Radicals: Assessment of HSO5− Activators

Abstract: The large production of wine and almonds leads to the generation of sub-products, such as winery wastewater (WW) and almond skin. WW is characterized by its high content of recalcitrant organic matter (biodegradability index < 0.30). Therefore, the aim of this work was to (1) apply the coagulation–flocculation–decantation (CFD) process with an organic coagulant based on almond skin extract (ASE), (2) treat the organic recalcitrant matter through sulfate radical advanced oxidation processes (SR-AOPs) and (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…It shows the operational conditions and the attained efficiencies. In Jorge et al [20], PMS was activated by cobalt ions in a UV-A LED reactor, for the treatment of WW. The conditions were revealed to be effective for sulfate radical activation, with 82.3% COD removal.…”
Section: Application Of Sulfate Radicals In Wastewater Treatmentmentioning
confidence: 99%
“…It shows the operational conditions and the attained efficiencies. In Jorge et al [20], PMS was activated by cobalt ions in a UV-A LED reactor, for the treatment of WW. The conditions were revealed to be effective for sulfate radical activation, with 82.3% COD removal.…”
Section: Application Of Sulfate Radicals In Wastewater Treatmentmentioning
confidence: 99%
“…The coagulation-flocculation (CF) process was performed in a Jar-test device (ISCO JF-4, Louisville, KY, USA), with four mechanical agitators powered by a regulated speed engine. Each coagulant was mixed with the samples of SW with a fast mix of 150 rpm/3 min and a slow mix of 20 rpm/20 min, at ambient temperature (25 • C), as described previously [4]. To optimize the CF process, different levels of pH (3.0, 6.0, natural and 9.0) and coagulant concentrations (0.1, 0.5, 1.0 and 2.0 g/L) were tested.…”
Section: Coagulation-flocculation Experimental Set-upmentioning
confidence: 99%
“…Moreover, the turbidity and TSS removal effectiveness slightly reduced as the pH value increased. Previous studies using plant-based coagulants reported that the negatively charged wastewater at lower pH may accelerate the adsorption process of the particles into protein-contained coagulants, increasing the turbidity and TSS removal [4,10]. Therefore, pH 3.0 was chosen to test different concentrations of coagulant.…”
Section: Coagulation-flocculation: Almond Hullsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of the CFD with AOPs, which are considered promising alternatives to degrading-or, at least, the turning into more biodegradable compounds of-recalcitrant organic matter through the generation of hydroxyl radicals (HO • ) [5]. These radicals have high oxidation potential; they are nonselective species, interacting with the pollutants and oxidizing them to CO 2 , H 2 O, and partly oxidized species [6].…”
Section: Introductionmentioning
confidence: 99%